2006
DOI: 10.1385/jmn:29:3:279
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-Associated MnSOD Induction Protects Against β-Amyloid-Induced Neuronal Apoptosis

Abstract: Expression of manganese superoxide dismutase (MnSOD), a nuclear-encoded mitochondrial primary antioxidant enzyme, is protective against various paradigms of oxidative stress-induced brain injury. We have shown previously that the presence of an intronic nuclear factor site, kappaB (NF-kappaB), in the MnSOD gene is essential for the induction of MnSOD by tumor necrosis factor alpha (TNF-alpha). However, whether activation of NF-kappaB is protective against oxidative stress-induced neuronal injury is unclear. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 48 publications
2
36
0
1
Order By: Relevance
“…In a related study the activation of NF-κB by a low dose of Aβ40 or Aβ25-35 involving ROS has been demonstrated in primary culture of neurons [89]. Consistent with the neuroprotective action of NF-κB activation, one study has reported that TNF-α treatment of SHSY5Y cells upregulates Mn-SOD gene through NF-κB activation which subsequently protects the cells from a challenge by amyloid beta peptide or ironmediated oxidative stress [101]. Another study identifies a resistant clone of PC12 cells against oxidative stress with constitutively high NF-κB activity [102].…”
Section: Nf-κb and Alzheimer's Diseasementioning
confidence: 74%
“…In a related study the activation of NF-κB by a low dose of Aβ40 or Aβ25-35 involving ROS has been demonstrated in primary culture of neurons [89]. Consistent with the neuroprotective action of NF-κB activation, one study has reported that TNF-α treatment of SHSY5Y cells upregulates Mn-SOD gene through NF-κB activation which subsequently protects the cells from a challenge by amyloid beta peptide or ironmediated oxidative stress [101]. Another study identifies a resistant clone of PC12 cells against oxidative stress with constitutively high NF-κB activity [102].…”
Section: Nf-κb and Alzheimer's Diseasementioning
confidence: 74%
“…However, the role of MnSOD in fALS pathogenesis remains elusive. MnSOD is expressed in almost all mammalian cells, including neurons, and can be induced under various conditions (10,16,37,50). We recently demonstrated that the molecular pathology of FUS mutation can be recapitulated in cell culture (20) and Drosophila (55) models.…”
Section: Discussionmentioning
confidence: 99%
“…Specific underlying physiological changes that occur post-LED therapy in this patient population are largely unknown. Data from animal and cellular studies, however, would suggest increase in ATP, 29,33,66,67 diffusion of nitric oxide promoting vasodilation 38 and rCBF in cortical areas, 31 an increase in antioxidants, 68 and decreased inflammation 39,69,70 as possible supporting mechanisms for improved function in the chronic stage. …”
Section: Potential Mechanismsmentioning
confidence: 99%